Drag Queen Performers in Urban Pink Tourism: Community of People, Place, and Poverty - Nazrina Zuryani; Tedi Erviantono; Nyoman Ayu Sukma Pramestisari (SOCIUS, 2022)
The research focuses on “front and back stage” such as exposed in in-depth interviews of two drag queens: Mami Salsa and Mami Sisca, the first one from Denpasar, the second from Singaraja in North Bali. Mami Salsa started working as a drag queen in the late 90s and retired from performing in 2020. Having had a wife and children, he dresses as a man and is now considered a senior drag queen; he is not in good health, so he rarely performs and instead mentors young drag queen performers. As for Mami Sisca, “she” stopped performing as a drag queen in November 2019 and now works as a popular English teacher for kids as well as a cat and dog rescuer. She still dresses as a woman, and having gained wide social recognition during her “front stage” drag queen days, “she” is now a respected figure of Singaraja’s community. Socially integrated, both Mami Salsa and Mami Sisca show the type of positive evolution of urban tourism that shows people, place and poverty as aspects of the lives of drag queens. One of the ways that could help ordinary drag queens to follow the steps of Mami Salsa and Mami Sisca would indeed be for the hotel and restaurant association to give full recognition to their performing arts profession. This research advocates the drag queens coalition of Bali to have the pocket book and the web site to make their profession sound and legal.